Surface functionalization of PEEK with silicon nitride. (11th December 2020) - Boschetto, Francesco; Marin, Elia; Ohgitani, Eriko; Adachi, Tetsuya; Zanocco, Matteo; Horiguchi, Satoshi; Zhu, Wenliang; McEntire, Bryan J; Mazda, Osam; Bal, B Sonny; Pezzotti, Giuseppe
Abstract: Surface roughness, bioactivity, and antibacterial properties are desirable in skeletal implants. We hot-pressed a mix of particulate sodium chloride (NaCl) salt and silicon nitride (β-Si3 N4 ) onto the surface of bulk PEEK. NaCl grains were removed by leaching in water, resulting in a porous PEEK surface embedded with sim15 vol% β-Si3 N4 particles. This functionalized surface showed the osteogenic and antibacterial properties previously reported in bulk silicon nitride implants. Surface enhancement of PEEK with β-Si3 N4 could improve the performance of spinal fusion cages, by facilitating arthrodesis and resisting bacteria.